Gut microbiota-derived short-chain fatty acids mediate the antifibrotic effects of traditional Chinese medicine in diabetic nephropathy - Jiang, Haiyan; Wang, Xiaoran; Zhou, Wei; Huang, Zhili; Zhang, Wen (Frontiers in Endocrinology, 2025)
Diabetic nephropathy (DN), a devastating microvascular complication affecting 40% of diabetic patients worldwide, represents the leading cause of end-stage renal disease (ESRD) and poses a substantial therapeutic challenge due to its complex pathogenesis involving progressive renal fibrosis. Note: Throughout this manuscript, we use “diabetic nephropathy (DN)” and “diabetic kidney disease (DKD)” interchangeably to refer to kidney disease resulting from diabetes mellitus, as both terms are recognized in current literature. Disruption of intestinal microbial balance contributes to the overproduction of uremic toxins such as indoxyl sulfate and p-cresyl sulfate, while reducing beneficial metabolites like short-chain fatty acids (SCFAs), thereby aggravating renal inflammation and fibrosis through the gut–kidney axis. Traditional Chinese medicine (TCM) offers therapeutic potential in DN by modulating the gut microbiota and their metabolic products. We aimed to investigate the therapeutic effects of TCM on DN progression, with a particular focus on gut microbiota-derived SCFAs and their downstream signaling pathways. In a streptozotocin-induced DN rat model, TCM treatment enhanced renal function, as demonstrated by a 40% reduction in serum creatinine (p<0.01) and a 60% reduction in albuminuria (p<0.001), while attenuating glomerular hypertrophy and tubulointerstitial fibrosis. The treatment restored gut microbial diversity (Shannon index increased from 2.5 to 4.1, p<0.05) and increased the abundance of SCFA-producing genera, including Lactobacillus, Roseburia, and Ruminococcus. Correspondingly, gas chromatography–mass spectrometry confirmed elevation of fecal concentrations of acetate, propionate, and butyrate (butyrate increased by 2.5-fold, p<0.01). At the molecular level, TCM upregulated renal expression of G protein-coupled receptors GPR41 and GPR43 and suppressed activation of the TGF-β1/Smad signaling pathway. Notably, antibiotic treatment abolished these renoprotective effects, whereas exogenous butyrate supplementation partially restored the antifibrotic outcomes. These findings collectively indicate that modulation of the gut microbiota–SCFA–GPR axis plays a pivotal role in alleviating DN-associated renal fibrosis, supporting its potential as a microbiota-targeted therapeutic strategy for improving renal outcomes in DN.